Halal antimicrobials in food: A review on prospects and challenges of antimicrobials from animal sources - Azman, Azid; Muhamad Shirwan, Abdullah Sani; Mohammad Aizat, Jamaludin (2020)
Food antimicrobial agents (FAA) provide the first food defence system against pathogens for processed food products. In addition, they function as an antioxidant in preventing colour and taste changes for food safety and quality. Muslim consumers are concerned about the source of FAA which may contain non-permissible ingredients according to Islam including pig and unslaughtered permissible animal sources. They also raise concerns about the increasing risk of toxicity when the FAA is consumed and the possibility of the FAA rendering organoleptic effect on the food. The application of the FAA protects the food from microbial contamination and indirectly combats emerging devastating diseases. Hence, halal FAA (HFAA) can be introduced so that Muslim consumers can accept FAA usage. Generally, HFAA is categorised according to ingredient sources such as animal, plant, bacteria, or synthetic origins. There are doubts on the halal status of animal-origin FAA as the source might be originating from pig, unslaughtered animal, human, or origins which are filthy. The animalorigin FAA shows strong antimicrobial properties against Gram-positive and negative pathogens, as well as toxicity and organoleptic issues. Thus, the FAA should be used within the allowable range. HFAA has become one of the most studied FAAs due to these issues. Many HFAAs are produced from animals without the full verification of halal status. This review presents an overview of the origins and challenges of HFAA production. Furthermore, this study also highlights how FAA could be verified as halal which is the theme of future research in HFAA development.